La visualidad del "Logos" trinitario: dogma y experiencia - López Hortelano, Eduard (Gregorianum, 2025)
The objective of this research is to determine the importance of Christ, the image of the invisible God, for theological and spiritual reflection and the experience of Christian faith. To do this, this article analyzes, first of all, the relationship between the image and imitation of Christ and the function of the Holy Spirit who shows what is imitable. This movement from top to bottom helps to get out of the self-referentiality of the baptized and is complemented, secondly, with a recovery of the eternal in front of the immediate, which allows adoration and ordering towards the divine. Thirdly, these aspects mark Christian existence from a contemplative perspective (elevation of the mind) to spiritual motions and missionary or apostolic commitment (the Christian follower and apostle).